The Process Of Transforming The Mahabharata Literary Work Written In The Old Javanese Into Geguritan Sarpayajnya And Geguritan Kicaka Written In The Balinese Language - I Made Suastika; I Ketut Jirnaya; I Wayan Sukersa; Luh Putu Puspawati (Institut Hindu Dharma Negeri Denpasar, 2017)
The story of the Pandawas and their wife in Wirata was used as the plot of the geguritan Kicakawhich was initially transformed from Wirataparwa in the form of Parwa. The only episode which was transformed into geguritan written in the Balinese language is the one narrating when the Pandawas were in disguise for one year. In this episode the love story of their wife, Drupadi, who was disguised as Sairindriis also narrated. In this episode it is also narrated that the Chief Minister, Kicaka, would like to have her as his wife. However, the Chief Minister, Kicaka, was killed by Bima, who was disguised as Ballawa, meaning that the love story came to an end. From the language point of view, the episode telling that the Pandawas were in Wirata was transformed into Geguritan Kicaka written in the Balinese language. In addition, although the text was dynamically translated, many Old Javanese words are still used in the Balinese version.Similarly, geguritan Sarpayajaya adopted the episode of Sarpayajnya of Adiparwa; however, the plot was modified again using thestrophes pangkur, dangdanggula, sinom and durma and was introduced using the Balinese language. It is narrated that King Parikesit was bitten and killed by a snake named Taksaka. Consequently, his son, Janamejaya, performed a ritual known as Sarpayajaya, causing all the snakes to die. From the cultural point of view, the text is recited as part of the performing art and the art of music ‘magegitan’ in Bali. The text Sarpayajayaisrecited as part of the cremation ceremony ‘ngaben’ known as mamutru.